The effects of intergroup competition on prosocial behaviors in young children: a comparison of 2.5–3.5 year-olds with 5.5–6.5 year-olds - Zhu, Yi; Guan, Xian; Li, Yansong (Frontiers in Behavioral Neuroscience, 2015)
Group-based competition is considered to be a ubiquitous social context in human society. However, little is known about its potential effects on children’s prosocial behaviors. To this end, we designed an experiment in which two age groups (2.5-3.5 years of age and 5.5-6.5 years of age) engaged in an intergroup competition task where they did a so-called ‘game’ where each child transferred table tennis balls with a spoon from one container to the other. The non-intergroup competition condition was identical to the intergroup competition condition with one exception- no intergroup competition manipulation was involved. Then, they were required to perform two economic games used to measure their prosocial behaviors. We found that under the non-intergroup competition condition, as children aged, their behaviors tended to be more fairness-oriented (such as an increase in egalitarian behaviors). However, under the intergroup competition condition, children at 2.5-3.5 years of age tended to behave prosocially towards their ingroup members compared with those who are at 5.5-6.5 years of age. Such behavioral pattern under the intergroup competition condition reflected strengthening prosocial tendencies driven by the intergroup competition in younger children and simultaneously weakening intergroup competition-driven prosocial tendencies possibly due to the development of fairness-oriented behaviors in older children. Taken together, these results point to the importance of considering effects of competitive contexts on children’s behaviors and may have important implications for further research on the role of competitive contexts in the development of human prosocial behaviors.